1992
DOI: 10.1021/ic00044a029
|View full text |Cite
|
Sign up to set email alerts
|

Platinum(IV)-mediated redox coupling of 2-propanone oximes in cis-[Pt(Me2C=NOH)2Cl4]. Crystal structure of [Pt(N(=O)CMe2ONCMe2)Cl2]

Abstract: The complex cis-[Pt(Me2C=NOH)2Cl2], 1, isomerizes into trans-[Pt(Me2C=NOH)2Cl2], 2, upon heating in the solid phase at 140 °C. Isomerization of 1 into 2 was also performed in acetonitrile or acetone solutions, containing catalytic amounts of Me2C=NOH; in the DMF-DMSO mixture, a 2-propanone oxime is displaced by DMSO in formation of cis-, 3, and ?rans-[Pt(Me2C=NOH)(DMSO)Cl2], 4. An excess of dimethyl sulfoxide results in the formation of the well-known complex cis-[Pt(DMSO)2Cl2]. Complex 4 has also been obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
31
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 1 publication
10
31
0
Order By: Relevance
“…Nevertheless, the Pt−N interatomic distances in 1 and 2 are 2.007(2) and 2.015(4) Å, respectively, which is consistent with those in the platinum(II) complex [PtCl( N , N -N(CMe 2 )C 2 H 4 NH 2 )(PBu 3 )]Cl (2.08(1) Å ) and in some oxime-containing Pt(II) complexes (1.97−2.02 Å , ). The C(6)−O(1) bond length (1.475(3) Å) in 1 and C(7)−O(2) bond length (1.472(6) Å) in 2 agree within 3σ with the C−O bond distance (1.55(3) Å) found earlier in [PtCl 2 (N(O)CMe 2 ONCMe 2 )] .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Nevertheless, the Pt−N interatomic distances in 1 and 2 are 2.007(2) and 2.015(4) Å, respectively, which is consistent with those in the platinum(II) complex [PtCl( N , N -N(CMe 2 )C 2 H 4 NH 2 )(PBu 3 )]Cl (2.08(1) Å ) and in some oxime-containing Pt(II) complexes (1.97−2.02 Å , ). The C(6)−O(1) bond length (1.475(3) Å) in 1 and C(7)−O(2) bond length (1.472(6) Å) in 2 agree within 3σ with the C−O bond distance (1.55(3) Å) found earlier in [PtCl 2 (N(O)CMe 2 ONCMe 2 )] .…”
Section: Discussionsupporting
confidence: 75%
“…Recently, we have demonstrated that the oxidation of cis -[PtCl 2 (RR‘CNOH) 2 ], where R = R‘ = Me, RR‘ = (CH 2 ) 4 and (CH 2 ) 5 , by molecular chlorine yields cis -[PtCl 4 (RR‘CNOH) 2 ] . The latter compounds, on standing in water−acetone solution, undergo an unusual spontaneous Pt(IV)-mediated redox coupling leading to the platinum(II) chelate [PtCl 2 (N(O)CRR‘ONCRR‘)], shown in Scheme .…”
Section: Introductionmentioning
confidence: 99%
“…The lp−πh interactions can be carbon- or heteroatom-directed (e.g., contacts involving carbonyls, amides, and carboxyls in peptides and other biopolymers, nitro groups in nitroalkenes, electron-deficient main group element compounds like BX 3 , AlX 3 , , a C atom in an electron-deficient arene, and the N atom(s) in a heterocycle; Figure , a1 ), bond-directed (e.g., with a double bond in the electron-deficient arene ring; , b1 ), or cycle-directed (e.g., with electron-deficient arenes and heterocycles, or even involving electron-rich aromatic rings; c1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the N(1)–O(1) and N(2)–O(3) bond distances are 1.364(7) and 1.367(7) Å (Figure ) and these values are close to N sp2 –O (1.394(18) Å in oximes) in bqoxH. The N(3)–O(3) and N(4)–O(4) bond lengths are 1.269(7) and 1.277(7) Å, and they are close to the NO bond length (1.265(5)–1.274(4) Å) in the radical-anion bqox •– ligands in the Ru II complexes, and smaller than the double NO bond (1.227(5)–1.243(3) Å in the Ru II -coordinated o -dinitrosobenze, 1.218(13) Å in the nitro group; ∼ 1.21 Å in metal-bound nitrosoalkanes ). The C(1)–N(1) and C(2)–N(2) bond lengths are 1.309(8) and 1.318(8) Å in bqox and the C(7)–N(3) and C(8)–N(4) bond lengths are 1.372(8) and 1.380(8) Å in bqox •– , respectively.…”
Section: Resultsmentioning
confidence: 76%